Between explicit and optional familialism. Shifts of childcare regime in Chile - Cecilia Montes Maldonado; William Vera Rojas; Carina De La Barra Urquieta (Punto Género, 2018)
During the last decade the Chilean pattern of childcare provision is changing due to the rise of female participation in the labor market, the fertility rates reduction, new forms of family organization, new social policies to care, among others. Based on a case study the article examines the childcare regime, analyzing three mechanisms of provision: extra-family services, paid and unpaid family work, and time to care. It is analyzed changes in this childcare pattern by using the conceptual categories of familialism, gender and social equity. This paper suggests that the Chilean model shifts from an explicit to an optional one. The gender equity is characterized by a weak maternalist and the social equity is showed segmented.